ISLAMIC INVESTMENT AND HOW TO TAKE ADVANTAGE OF CAPITAL (THE CASE OF GLOBAL MERCHANTS IN THE CITY OF MATARAM, LOMBOK, INDONESIA) - Busaini Busaini (Universitas Airlangga, 2018)
This paper describes how the economic development of Islam in Indonesia and Islamic investment offender, specific investment is viewed from two musty mudharabah and ijarah. We know people are familiar with conventional investments that rely on the interest rate, but the author tries to see a bunch of people who do not invest based on the interest rate. Community groups in question are gold and pearl merchants in the city of Mataram; they traded with the islamic law principle informed with the actual quality of the goods, weighing, and make an appointment with either. Associated with investments, they provided capital among traders with profit sharing agreement at the end of the year, 60 percent to 40 percent owner of capital for business managers. Labor they take an average of 2 people for each trader with wage system 50 thousand rupiahs per day. Contribution to the development of economic gold traders Mataram is helpful in employment, supporting the development of West Nusa Tenggara Tourism, both domestic and abroad, especially in the area of increased income tax payments, an increase in the welfare of the community with many traders who perform the Hajj.